A prototype portal for Worldwide Church of God, Malaysia / Roginidevi Venggumany - Roginidevi , Venggumany (2003)
With the tremendous growth of the Internet and the expansion of the Internet and the expansion of the World Wide Web, more and more facility and information is being put on the internet. The Internet create a global communication that break the barrier of time, place and distance within which conducts a Prototype Portal for Worldwide Church of God, Malaysia. A Prototype Portal for WCG, Malaysia is a system that allows worldwide people to create their own community through the Internet for the propose like communicate to each other or sharing information. This thesis describe the system that allows Internet user sharing information, news, idea at anywhere at any time through the Internet. A Prototype Portal for Worldwide Church of God, Malaysia has several modules. Structure diagram used to show an overall subsystem of the project. Besides, this project will review the method, technologies and development tools (like waterfall model with prototyping, using ASP on windows 2000 platform, the web server with back-end database Microsoft SQL Server 7.0) that are used to set up this system. At the end, this project will implement the entire requirement into a real system and analysis the strengths and weakness of the system. It is hope that the major problems faced by current system can be solved through this project.